Briefing: Decarbonising buildings in Europe: a briefing paper. Issue 4 (24th November 2021) - Norton, Brian; Gillett, William B.; Koninx, Felix
Abstract : Energy used to provide heating, cooling and ventilation in buildings supplied using fossil fuels produces about 25% of total European (EU) greenhouse gas (GHG) emissions. To reduce this requires lower energy use in both existing and future buildings with the remaining energy supplied from very-low-carbon sources. This briefing paper discusses how to reduce the GHG emissions from buildings in Europe to nearly zero. Coordinated updating of existing policies together with well-targeted and innovative EU, national and local initiatives are required to deliver the required reductions. It will be important to ( a ) ensure that measures to reduce energy and GHG reductions also enhance the health and well-being of building occupants, ( b ) integrate decarbonisation of electricity and heat supplies for buildings with decarbonisation of industry and transport, ( c ) reuse and recycle to reduce embodied GHG emissions in building materials, components and processes used in both the construction of new buildings and in building renovations. Decarbonising buildings is an opportunity to develop and produce new products and services that create new high-quality jobs.